Reconceptualizing Pain: Integrating Neuroscience, Psychology, and Spirituality in Understanding Student Suffering - Petrova, Anna (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2013)
Pain has traditionally been interpreted within biomedical frameworks that conceptualize it primarily as a physiological response to tissue damage or neurological dysfunction. However, increasing evidence from neuroscience, psychology, and medical humanities suggests that pain is a complex and multidimensional phenomenon shaped by biological, emotional, cognitive, and spiritual processes. This article proposes a theoretical framework that integrates insights from neuroscience, psychological theory, and spiritual traditions in order to reconceptualize pain as a holistic human experience. Drawing on interdisciplinary literature, the study examines how neural mechanisms, emotional regulation, cognitive interpretation, and spiritual meaning-making interact in shaping pain perception. The analysis highlights the limitations of reductionist biomedical models and emphasizes the importance of integrative approaches that acknowledge the mind–body–spirit connection. The proposed framework suggests that pain experiences emerge from dynamic interactions among physiological signals, psychological interpretation, and existential meaning systems. By synthesizing contemporary scientific research with insights from philosophy and spirituality, this study contributes to the development of a biopsychosocial–spiritual model of health. The article concludes that effective responses to chronic pain require interdisciplinary collaboration and healthcare systems that address not only physical symptoms but also emotional wellbeing and existential dimensions of human suffering.